Measuring the effectiveness of road transportation logistics performance in east Malaysia: A conceptual model - Nur Fadiah Mohd Zawawi; Sazali Abd Wahab; Abu Sofian Yaacob; Naresh Kumar Samy; Syed Ali Fazal (Canadian Center of Science and Education, 2016)
The successful of any tasks or jobs entrusted to logistics service providers is measured by performance. A good performance means the logistics service providers succeed in fulfilling customers’ requirements and perceptions. Among customers’ requirements are delivery of goods on-time, reasonable costs, the safety of their goods and so forth. However, nowadays this performance is being disturbed by road congestion problems due to the flooding of road logistics transportations which are used to deliver products or goods to their customers, together with the addition of public road transportation. As a result, the delivery of customers’ goods is delayed and the operation costs also increased. This hustle and bustle happens since the global manufacturing sector grows dramatically these days. Consignees do not agree with several solutions to this issue, since it is found to be favouring the customers, without any concern to the consignees themselves. Hence, this study adapted several previous models in order to come out with a new model which can prevent delivery delay and reduce operation cost. This is a promise for an effective and efficient logistics service providers’ performance. With regards to the prior literature, the capability of logistics service providers is very valuable to maintain the good performance of a logistics firm, IT implementation is empirically proven as an enabler for time and cost saving, and innovation capability is important in differentiating one firm to another. Hence, it can sustain the competitive performance and advantages. Therefore, the formation of the mentioned variables has constructed a new model for this study which is expected to benefit logistics service providers to improve their services and simultaneously provide a nice picture to potential investors to invest in our country, Malaysia.